Deteksi Dini Keseimbangan Statis dan Penerapan Core Stability Exercise pada Lansia Di Kebak Kalang, Karanganyar - Pristianto, Arif; Apriliyani, Yuyun; Azizi, Laili Rahmawati; Putri, Fauzia Alya; Yasmin, Safira Yulia (Journal of Appropriate Technology for Community Services, 2024)
The elderly is a person who has entered the age of over 60 where changes in his body begin to take place, both visible and invisible changes. One apparent change is that physical and functional changes can cause the lack of muscle in the body. Postural muscle weakness can be fatal to one of these balancing disorders. Balance is the body's ability to maintain position in either silence or movement. The purpose of this devotion is to detect early, static balance in the elderly with functional reach test. Beyond that, to find out the effectiveness of the core returned home administration and gymnastics to enhance the delicate balance of stasis. This method of devoted activity includes observation, preparation, performance and evaluation of activities. The results of giving the core stability exercise and gymnastics have proven to improve the elderly's balance significantly. This is demonstrated by an increase in the measuring of balance from a starting value of 32% to 71.4%.